2020
DOI: 10.1186/s13550-020-00676-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of dopamine transporter PET measurements with [18F]FE-PE2I in patients with Parkinson’s disease

Abstract: Background: Reliable quantification of dopamine transporter (DAT), a biomarker for Parkinson's disease (PD), is essential for diagnostic purposes as well as for evaluation of potential disease-modifying treatment. Due to degeneration of dopaminergic neurons and thus lower expected radioligand binding to DAT, higher measurement variability in PD patients might be expected than earlier reproducibility results in healthy controls. Therefore, we aimed to examine the test-retest properties of [ 18 F]FE-PE2I-PET in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In 2012, [ 18 F]FE-PE2I showed promising results in 10 healthy subjects [ 16 ] and this was substantiated by Shingai and co-workers [ 17 ] who found an age-related decline in DAT density of approximately 7.5% per decade in the caudate and putamen and 3.4% in substantia nigra. Reproducibility over time of PET measurements with [ 18 F]FE-PE2I demonstrated good agreement in twelve healthy male subjects[ 18 ] and later in nine PD patients [ 19 ], making [ 18 F]FE-PE2I PET feasible for studying long-term alterations in DAT availability. Based on dynamic [ 18 F]FE-PE2I PET scans in PD and healthy subjects, Sonni et al [ 20 ] suggested that static imaging during early peak (17–42 min after injection) could be used as a simplified quantification method compared to the full quantification using long dynamic acquisitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, [ 18 F]FE-PE2I showed promising results in 10 healthy subjects [ 16 ] and this was substantiated by Shingai and co-workers [ 17 ] who found an age-related decline in DAT density of approximately 7.5% per decade in the caudate and putamen and 3.4% in substantia nigra. Reproducibility over time of PET measurements with [ 18 F]FE-PE2I demonstrated good agreement in twelve healthy male subjects[ 18 ] and later in nine PD patients [ 19 ], making [ 18 F]FE-PE2I PET feasible for studying long-term alterations in DAT availability. Based on dynamic [ 18 F]FE-PE2I PET scans in PD and healthy subjects, Sonni et al [ 20 ] suggested that static imaging during early peak (17–42 min after injection) could be used as a simplified quantification method compared to the full quantification using long dynamic acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the use of [ 18 F]FE-PE2I in substantia nigra and report a less pronounced reduction of [ 18 F]FE-PE2I levels compared to striatum [ 22 24 ]. Repeatability and reliability have been shown to be very high in striatum with a variability of 5–7% and an intraclass coefficient of 0.91, but only modest in substantia nigra due to the smaller size and DAT density [ 19 ]. The effect size for discrimination between PD patients and healthy controls using [ 18 F]FE-PE2I PET as compared to [ 123 I]FP-CIT SPECT was found to be at least as good by Mo et al [ 25 ] in 22 presumed early-stage PD patients and 28 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The first cohort consists of twenty PD patients of which the baseline DAT PET data have already been reported ( Fazio et al, 2018 ). The second cohort consists of twenty PD patients of which the baseline PET of some were part of the previously reported test–retest study ( Kerstens et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This property was also confirmed in a subsequent healthy human PET study ( Fazio et al, 2015 ). Test-retest studies in healthy controls ( Suzuki et al, 2014 ) and non-advanced PD patients ( Kerstens et al, 2020 ) have shown good reliability and repeatability of [ 18 F]FE-PE2I PET measurements also in small or lower DAT density regions such as the substantia nigra. Recently, [ 18 F]FE-PE2I has also been included in the EANM guideline and SNMMI procedure standard for clinical DAT imaging in Parkinsonian syndromes ( Morbelli et al, 2020 )).…”
Section: Introductionmentioning
confidence: 99%
“…The imaging of DAT was used as a potential surrogate marker for dopaminergic neurons in nigrostriatal pathway. DAT mediates the transport of dopamine and DAT availability is restricted to dopaminergic neurons [ 41 , 42 ]. The analysis of DAT was conducted to further explain the observed motor function.…”
Section: Methodsmentioning
confidence: 99%